Reproducing colonial imaginaries: the festival and the social representation of the «tacneño» and the Andean «migrant» in the local press of Tacna (Peru) - Pastor Seperak, Marly Mahly (2025)
Based on the analysis of local newspaper reports (from 1980 to 2010) regarding three popular festivals associated with the cultural practices of Andean migrants in Tacna (Peru), this article identifies and characterizes the social representation of this social actor in the discourse disseminated by the local press during that period regarding the festivals of Las Cruces, the Virgin of Copacabana, and Carnival. A process of stigmatization is observed around religiosity, hygiene, and urbanity that collide with the hegemonic representation of the cultural practices of the «Tacneño» (inhabitant of Tacna), and a discourse of control over religious and festive practices, thereby constructing identity differentiation and promoting physical and symbolic exclusion from the cultural practices of Andean migrants. The article argues that the press in Tacna has contributed to the configuration of a social imaginary of the «Tacneño» and the «migrant» based on the dichotomy of modernity/barbarism, giving rise to two divergent social representations.